Overall precision test of near infrared spectroscopy on mango fruits (Mangifera indicaCV. Nam Dok Mai Si Thong) by on-line and off-line systems - Wachiraya Lekhawattana; Panmanas Sirisomboon (My University, 2020)
The near infrared (NIR) spectroscopy both on-line and off-line scanning was applied on mango fruits (Mangifera indica CV. ‘Nam dok mai- si Thong’) for the overall precision test. The reference parameter was total soluble solids content (Brix value). The results showed that the off-line scanning had a higher accuracy than on-line scanning. The scanning repeatability of the off-line and on-line systems were 0.00199 and 0.00993, respectively. The scanning reproducibility of the off-line and online systems were 0.00279 and 0.00513, respectively. The reference of measurement repeatability was 0.2. The maximum coefficient of determination (R 2 max ) of the reference measurement was 0.894.
Keywords: Mangifera; Repeatability; Line (geometry); Spectroscopy and Chemometric Analyses